The Conformity of Diagnostic Test Between Burrow Ink Test Method With Skin Scrapping Method of Scabies in Rabbit (Lepus domesticus) - Fadila Zikri Amanda; Poedji Hastutiek; Emy Koestanti Sabdoningrum; Nunuk Dyah Retno Lastuti; Endang Suprihati; Hana Eliyani (Universitas Airlangga, 2018)
This study intend to know the conformity of diagnostic test between burrow ink test method with skin scrapping method of scabies in rabbit. Scabies caused by Sarcoptes scabiei which has a predilection in stratum corneum and lucidum. Clinical symptoms was characterized by papula or crusting of the skin. This study presents a laboratory explorative research with cross sectional approach. Samples used 20 rabbits that infested scabies naturally. Data obtained by performing diagnostic burrow ink test method and skin scrapping in rabbits which are infested scabies naturally. KAPPA test used as data analysis. Results showed that the number of positive results based on burrow ink test method are 12 rabbits and 8 rabbits are negative while skin scrapping obtained the positive results are 11 rabbits and 9 rabbits are negative. KAPPA test analysis performed on the overall study data was obtained 0,490. The conclusion of this study is burrow ink test method has a good conformity with the skin scrapping in rabbits which are infested scabies naturally that can be used for diagnostic analysis of scabies with a simple method, faster, and have the same ability with skin scrapping without hurting animals.